2017
DOI: 10.1111/hequ.12116
|View full text |Cite
|
Sign up to set email alerts
|

Should Gender Differences be Considered When Assessing Student Satisfaction in the Online Learning Environment for Millennials?

Abstract: The majority of today's students in online higher education are millennials and have grown up using technology. Therefore, there is a need to determine if their expectations from online learning are different from previous contextual studies and whether or not these vary across gender. This study used a mixed method approach, using focus groups, followed by online surveys of 834 undergraduate students from the University of Mauritius enrolled in an online course. Using factor analysis and structural equation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 40 publications
(64 reference statements)
9
51
2
1
Order By: Relevance
“…Though, perception and intention of elearning systems may depend on gender but the literature showed no conclusive evidences in this regard. Prior research showed noteworthy differences for male and female in critical success factors of technology adoption and acceptance [8].…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Though, perception and intention of elearning systems may depend on gender but the literature showed no conclusive evidences in this regard. Prior research showed noteworthy differences for male and female in critical success factors of technology adoption and acceptance [8].…”
Section: Gendermentioning
confidence: 99%
“…Furthermore, gender based analysis reported that BI depend on PU and PEOU are stronger in males in the adoption of e-learning systems [8]. Later on, another study conducted in Brazil analyzed that intention and usage behavior is more prevalent in male rather in female [10].…”
Section: Gendermentioning
confidence: 99%
“…This result agreed with various studies results which confirm the interactions between the teacher of the course and the students, and among students themselves, were important to the learning process. Also the interaction at appropriate time between the teacher and the learner was definite in strengthen/ reinforcement student learning, and the immediate and quick feedback from the teacher at appropriate time are essential key to achieve learners satisfaction about e-learning environment (Harrati et al, 2016;Harvey et al, 2017;Raspopovic & Jankulovic, 2017;Violante & Vezzetti, 2015;Virtanen et al, 2017;Wu et al, 2010).…”
Section: The Interpretation Of Research Resultsmentioning
confidence: 99%
“…To specify the scale dimensions, terms, backgrounds, theoretical attitudes, and various concepts in E-leaning field. E-learning environment satisfaction, were accessed, and to benefit from some literature reviews included used tools and measurements (Chang, 2011;Harrati, Bouchrika, Tari, & Ladjailia, 2016;Harvey, Parahoo, & Santally, 2017;Raspopovic & Jankulovic, 2017;Violante & Vezzetti, 2015;Virtanen et al, 2017;Wu, Tennyson & Hsia, 2010). This scale enrolled 36 phrases presented in 5 dimensions: The facility of using the systems, System functions, Interactions, Feedback provision synchronism, Overall satisfaction with learning environment.…”
Section: E-learning Environment Satisfaction Scalementioning
confidence: 99%
See 1 more Smart Citation